2020
DOI: 10.3389/fpsyg.2020.01836
|View full text |Cite
|
Sign up to set email alerts
|

Global Psychological Implications of Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Coronavirus Disease-2019 (COVID-19). What Can Be Learned From Italy. Reflections, Perspectives, Opportunities

Abstract: On December 31, 2019, the Chinese authorities announced that in the city of Wuhan, Hubei Province, central-eastern China, a cluster of pneumonia cases of unknown etiology had developed. A new coronavirus (SARS-CoV-2) that causes serious problems like pneumonia and even death, has been discovered. This new disease (COVID-19) has spread also in Italy starting from the first recognized case on February 20. Beyond its biological implications, this coronavirus allows us many psychological reflections. A new virus i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 15 publications
(21 citation statements)
references
References 54 publications
1
20
0
Order By: Relevance
“…It is beyond doubt that this decision helped to prevent the further spread of the virus and was a necessary imposition to limit the number of patients being admitted to hospital. Nevertheless, from a psychological point of view, people undergoing this first form of intervention were exposed to feelings of uncertainty, fear, anger, and frustration that may easily lead to anxiety, boredom, and/or uneasiness ( Brooks et al, 2020 ; De Giorgio, 2020 ; Holmes et al, 2020 ; Rubin and Wessely, 2020 ; Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…It is beyond doubt that this decision helped to prevent the further spread of the virus and was a necessary imposition to limit the number of patients being admitted to hospital. Nevertheless, from a psychological point of view, people undergoing this first form of intervention were exposed to feelings of uncertainty, fear, anger, and frustration that may easily lead to anxiety, boredom, and/or uneasiness ( Brooks et al, 2020 ; De Giorgio, 2020 ; Holmes et al, 2020 ; Rubin and Wessely, 2020 ; Wang et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent reviews indicated that the short-term psychological consequences included post-traumatic and depressive symptoms, high perceived stress, and an increase in anxiety and sleep disorders. 6,[12][13][14][15] A study carried out during the first three weeks of the lockdown in Italy indicated that 37% of participants experienced post-traumatic stress, while 17-23% reported significant levels of anxiety, perceived stress, and adjustment disorders 16 . Some authors underlined that such effects can be pervasive and long-lasting, suggesting that the exposure to the psychological stress experienced during the "quarantine" and the consequent social isolation can provoke long-term effects for mental health 17,18 As reported by Gruber et al 19 , there are three peculiar and unique ways in which the COVID-19 pandemic is a stressor able to adversely affect mental health in global population.…”
Section: Introductionmentioning
confidence: 99%
“…The COVID-19 became pandemic in March 2020 as stated by the World Health Organization (WHO). Until this paper was written, institutions and individuals are still struggling with the COVID-19 pandemic and all of its implications (De Giorgio, 2020).…”
Section: Introductionmentioning
confidence: 99%
“…The uncertain feeling is towards the government, the health care system, and the duration of the existing pandemic. Quarantine, | 8 lockdown, confinement, any mitigation forms, and social distancing will make anxiety and fear worsened (De Giorgio, 2020). Social mitigation during the COVID-19 pandemic will give a big threat to physical human connection, individual mental health, motivation, and brain profile in general (Hagerty & Williams, 2020).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation